MENGEMBANGKAN SIKLUS PENERAPAN SISTEM MANAJEMEN KINERJA BERBASIS KEMASLAHATAN - Firdaus, Achmad (Universitas Negeri Surabaya, 2018)
The study aims to develop the cycle of maslahah based performance management system (maslahah performa) implementation. Maslahah performa consists of 6 orientations are: worship orientation, internal process orientation, learning orientation, talent orientation, customer orientation and wealth orientation. The study is conducted through in-depth literature study of previous study related to the concept of maslahah, maslahah based performance management system, the balanced scorecard (BSC) and the quality management system. The study shows that maslahah performa can be applied with the foundation of PDCA cycle that is Plan - Do - Check - Action. Plan is developed into 5 steps: strategic planning, identifying the foundation of maslahah, determining the maslahah behavior, determining measures and agreeing the performance contract. Do is developed into performance implementation. Check is developed into monitoring process. Action is developed into corective and preventive action.